“The People Deserve Better Governance”: Examining the Letters of Filipino High School Students to the Next President of the Philippines - Wui, Ma. Glenda (Archīum Ateneo, 2024)
The study examined the results of the civic writing project “Letter to the Next President of the Philippines,” where grades 9-10 students were asked to write a letter to the next president about social problems that they wanted their future leader to resolve and why. The study analyzed the students’ letter topics according to their school type and location, gender, and the students’ sources of information for their civic writing. The letters (N=322) were written by students from urban and rural, and public and private schools across the country in March-May 2022 before the Philippine presidential election. The quantitative analysis shows that most students wrote about the following topics: poverty, education, corruption, unemployment, environment, low wages, illegal drugs, increasing price of basic needs, health, discrimination, and COVID-19. Chi-square test results show that six letter topics out of the 11 most chosen were significantly associated with the students’ school type and location. However, nonE were associated with gender. Most students relied on social media and conversations with parents/elders as sources of information for their writing. Implications of enhancing civic engagement through civic writing were discussed.